Effect of Proteolytic Enzymes (Bromelain and Papain) on Sensory and Chemical Quality of Sukuti (an Indigenous Dried Meat Product of Nepal) - Bhattarai, Kabindra; Lamichhane, Suman (Himalayan Journal of Science and Technology, 2021)
The present work was undertaken to compare the effect of bromelain and papain on the sensory quality of sukuti (Nepalese indigenous dried buffalo meat). Buffalo lean meat (round cut) was purchased from the local market of Dharan and used for the preparation of sukuti after injection of 10% m/m enzyme (bromelain and papain) solution at the concentration (0-100 mg/L) and resting for 4h followed by drying at 65°C up to the moisture of 5%. The optimized concentration of each enzyme was selected by sensory evaluation based on color, flavor, texture, and overall acceptability. The proximate composition, collagen content, and collagen solubility were studied for two optimized samples with enzyme treatment and control. The best tenderizing effect of papain and bromelain enzyme was found at 40 mg/L and 10 mg/L respectively from the sensory analysis and the sensory attributes for these concentrations were significantly (p